Batasan Pembelaan Korban Terpaksa : Peran dalam Tindak Pidana Begal - Maulana Maulana; Tamam Tamam (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This journal aims to enhance public understanding of the limitations of necessary defense (noodweer) in the context of robbery crimes (begal) in Indonesia. Necessary defense is a concept in criminal law that allows individuals to protect themselves or others from unlawful attacks that threaten safety, honor, or property. In the context of robbery crimes, where victims often face direct threats to their lives and safety, it is crucial to understand the conditions that must be met for this defense to be legally valid. This research employs a normative legal approach with an analysis of the Indonesian Penal Code (KUHP) and related literature. The findings indicate that while necessary defense is recognized in law, its application must consider proportionality and the underlying circumstances of the actions taken. Thus, this paper aims to provide a better understanding of necessary defense in robbery cases and its implications for law enforcement in Indonesia.